Decision tree based user-centric security solution for critical IoT infrastructure. (April 2022) - Puthal, Deepak; Wilson, Stanly; Nanda, Ashish; Liu, Ming; Swain, Srinibas; Sahoo, Biswa P.S.; Yelamarthi, Kumar; Pillai, Prashant; El-Sayed, Hesham; Prasad, Mukesh
Abstract: Data processing in real-time brings better business modeling and an intuitive plan of action. Internet of things (IoT), being a source of sensitive data collected and communicated through either public or private networks, requires better security from end to end to uphold integrity, quality, and acceptability of data. Designing an adaptive solution plays a vital role where IoT is deployed for the sensing-as-a-services in the critical infrastructure and near real-time decision making by deploying data analysis in the edge datacenters. Again, securing the system with user's demand and device specifications is a challenging and open research problem. This paper proposed a decision tree based user-centric security approach named D e c i s i o n T S e c that provides a secure channel for communication in IoT networks, combining edge datacenters in the network edges. Further, the proposed D e c i s i o n T S e c is validated by experimenting with the real-time testbed for the system performance along with the theoretical security validation.